Primary Cultures of Female Swine Genital Epithelial Cells In Vitro: a New Approach for the Study of Hormonal Modulation of Chlamydia Infection - Guseva, Natalia V. (American Society for Microbiology, 2003)
Previous studies have demonstrated that female reproductive hormones influence chlamydial infection both in vivo and in vitro. Due to the reduced availability of human genital tissues for research purposes, an alternative hormone-responsive model system was sought to study chlamydial pathogenesis. Mature female swine eliminated from breeding programs were selected as the animals of choice because of the similarity of a sexually transmitted disease syndrome and sequelae in swine to a disease syndrome and sequelae found in humans, because of the near identity of a natural infectious chlamydial isolate from swine to Chlamydia trachomatis serovar D from humans, and because a pig's epithelial cell physiology and the mean length of its estrous cycle are similar to those in humans. Epithelial cells from the cervix, uterus, and horns of the uterus were isolated, cultivated in vitro in Dulbecco's minimum essential medium-Hanks' F-12 (DMEM-F-12) medium with and without exogenous hormone supplementation, and analyzed for Chlamydia suis S-45 infectivity. The distribution of chlamydial inclusions in swine epithelial cells was uneven and was influenced by the genital tract site and hormone status. This study confirmed that, like primary human endometrial epithelial cells, estrogen-dominant swine epithelial cells are more susceptible to chlamydial infection than are progesterone-dominant cells. Further, the more differentiated luminal epithelial cells were more susceptible to infection than were glandular epithelial cells. Interestingly, chlamydial growth in mature luminal epithelia was morphologically more active than in glandular epithelia, where persistent chlamydial forms predominated. Attempts to reprogram epithelial cell physiology and thereby susceptibility to chlamydial infection by reverse-stage, exogenous hormonal supplementation were unsuccessful. Freshly isolated primary pig epithelial cells frozen at −80°C in DMEM-F-12 medium with 10% dimethyl sulfoxide for several weeks can, after thawing, reform characteristic polarized monolayers in 3 to 5 days. Thus, primary swine genital epithelia cultured ex vivo appear to be an excellent cell model for dissecting the hormonal modulation of several aspects of chlamydial pathogenesis and infection.